1988
DOI: 10.1080/00288233.1988.10421359
|View full text |Cite
|
Sign up to set email alerts
|

Foot scores of cattle 2. Relationships among measurements of feet from slaughtered steers from eight sire groups

Abstract: Objective linear measurements were taken at slaughter on the front and rear feet excised from 87 Angus-sired steers by known sires and dams. Generally, means for front foot traits were similar to those for rear feet, including a difference of only 2.0 0 in angle of front v. rear foot. The repeatability of objectively measured traits was high (>0.76). Correlations between measures on adjacent digits were high (0.54 -0.88), as were most correlations between data from front and rear feet. c;oeffi~ients of variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In contrast, claw angles decreased with age of dairy heifers in a study of Vermunt (1990), but lengths of the dorsal border and heel depths increased with age. Morris and Baker (1988) found in accordance that cattle with a higher body weight, which is comparable to age, had larger claws. Ral (1990) reported that toe length and heel height increased with higher lactation number in cows.…”
Section: Claw Conformationsupporting
confidence: 68%
See 1 more Smart Citation
“…In contrast, claw angles decreased with age of dairy heifers in a study of Vermunt (1990), but lengths of the dorsal border and heel depths increased with age. Morris and Baker (1988) found in accordance that cattle with a higher body weight, which is comparable to age, had larger claws. Ral (1990) reported that toe length and heel height increased with higher lactation number in cows.…”
Section: Claw Conformationsupporting
confidence: 68%
“…Similar observations in ewes were found by and furthermore, the authors worked out significant differences in DA of front claws and rear claws in eight weeks old lambs. Morris and Baker (1988) reported that claw angle in steers was greater in front claws. Most of the dimensions of claw traits differ significant between front and rear claw in cattle (Baumgarter, 1988;Baumgarter and Distl, 1990;Vermunt, 1990;Distl, 1996).…”
Section: Claw Conformationmentioning
confidence: 98%
“…No consideration seems to have been given to breeding stock with larger hoof surface areas to reduce ground pressures. there is evidence for sire effects on hoof area in Angus beef animals (morris & Baker 1988), and an investigation of the potential to breed dairy cows with big, flat feet is warranted. the mechanical hoof used by Di et al (2001) to simulate animal treading could be modified to investigate hoof-size impacts on soils.…”
Section: Reducing Hoof Impactsmentioning
confidence: 99%